CHALLENGES FACED BY 11 TH-GRADE STUDENTS AT SMAN 1 INDRALAYA UTARA IN READING ENGLISH TEXTS - Febrina Berliana; Hesti Wahyuni Anggraini (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study investigates the reading difficulties faced by eleventh-grade students at SMA N 1 Indralaya Utara and explores the strategies they use to overcome them. A Mixed-Method approach with a Sequential Explanatory Design was employed. In the first phase, quantitative data were gathered through a reading comprehension test and a Likert-scale questionnaire administered to 71 students. The results revealed that the most common challenges were analyzing sentence structure (28%) and understanding vocabulary (26%), followed by interpreting discourse and comprehending texts (23% each). In the second phase, semi-structured interviews with selected students of different reading proficiency levels were conducted to explore these challenges more deeply. Thematic analysis was used to identify key themes such as vocabulary difficulties, syntactic confusion, discourse interpretation, and strategic or external support efforts. The integration of both quantitative and qualitative findings provides a comprehensive understanding of students’ reading comprehension problems and highlights the need for more targeted instructional support in grammar awareness, vocabulary enrichment, and reading strategy training.